Children's responses to the screen : a media psychological approach - Valkenburg, Patti M., 1958- (LEA's communication series., 2004)
There have been thousands of studies into children and the media. Yet, much academic research is still in its infancy when it comes to our knowledge about the uses, preferences and effects of different media. This volume moves the field forward in this regard, with its insights into the latest theories and research on children and the media.